sol4 - n b n = 0. Thus it follows from Theorem 11.3.12 that...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Let a n be the sequence a n = n ± cos ± 1 n - 1 (1) Observe that if we call: f ( x ) = cos( x ) - 1 x (2) and b n = 1 n (3) then we have a n = f ( b n ) (4) We know that, after setting f (0) = 0, f ( x ) is a continuous function for all x real. Moreover lim
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: n b n = 0. Thus it follows from Theorem 11.3.12 that lim n a n = f lim n b n = f (0) = 0 (5) 1...
View Full Document

This note was uploaded on 05/23/2010 for the course MATH 1501 taught by Professor N/a during the Fall '08 term at Georgia Institute of Technology.

Ask a homework question - tutors are online